Centipede predation on vertebrates: a review with the first bat case from Asia - Kamalakannan, Manokaran; Mondal, Rahul; Banerjee, Dhriti (Frontiers in Ecology and Evolution, 2025)
Centipedes (Chilopoda: Scolopendromorpha), long regarded as generalist arthropod predators, are increasingly recognized for their capacity to subdue and consume small vertebrates. This review synthesizes over a century of published accounts documenting centipede predation on amphibians, reptiles, birds, mammals, and occasionally fish, emphasizing the ecological breadth, behavioral strategies, and taxonomic diversity of both predators and prey. Notable cases include Scolopendra gigantea preying on bats in Venezuelan caves, Scolopendra subspinipes capturing snakes in urban environments, and Cormocephalus coynei exerting top-down control on seabird populations on predator-free islands. We also present the first confirmed case of bat predation by a centipede in Asia, where a Rhysida species was observed consuming a Pipistrellus bat in a fig tree hollow in West Bengal, India. This observation expands the known biogeography and ecological context of vertebrate predation by centipedes. Our synthesis highlights the underappreciated role of scolopendrid centipedes as mid-level predators capable of influencing small vertebrate populations, particularly in resource-limited or insular ecosystems, and calls for a re-evaluation of their functional position within terrestrial food webs.